Internalization of Religious Moderation Values For Students In MAN 2 Palembang - Siti Zailiah (Edukasi Islami: Jurnal Pendidikan Islam, 2022)
This article is related to how to internalize the values of religious moderation for students in Madrasah Aliyah Negeri 2 Palembang. This is qualitative field research, namely data obtained directly from the field through observations, interviews, and documents. In this study, researchers used a qualitative descriptive approach and received data in the form of written and spoken words and explained them in detail and detail. Data collection techniques in this study are through interviews, observation, documentation, and triangulation. Data analysis techniques start from data collection, presentation, and verification. From the results of the study, it can be concluded that four indicators of religious moderation, namely national commitment, tolerance, nonviolence, and accommodating to local culture, have all been carried out well by the indicators of Religious moderation, such as the national commitment by instilling values to students through the learning process, love for the homeland is one form of having a very high commitment to the nation. Tolerance by maintaining a balance between citizens in the educational environment and the community. Accepting existing differences does not disturb if others express opinions and express their beliefs. Nonviolence by instilling the value of peacefully expressing ideas and understanding of religion so as not to cause violence mentally, physically, or verbally. Accommodating to Local Culture, with preservation carried out continuously, directed, and integrated to realize specific goals that reflect the existence of something fixed and eternal, dynamic, flexible, and selective.